2020
DOI: 10.1038/s41598-020-71263-9
|View full text |Cite|
|
Sign up to set email alerts
|

Co-targeting PIM and PI3K/mTOR using multikinase inhibitor AUM302 and a combination of AZD-1208 and BEZ235 in prostate cancer

Abstract: PIM and PI3K/mTOR pathways are often dysregulated in prostate cancer, and may lead to decreased survival, increased metastasis and invasion. The pathways are heavily interconnected and act on a variety of common effectors that can lead to the development of resistance to drug inhibitors. Most current treatments exhibit issues with toxicity and resistance. We investigated the novel multikinase PIM/PI3K/mTOR inhibitor, AUM302, versus a combination of the PIM inhibitor, AZD-1208, and the PI3K/mTOR inhibitor BEZ23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Cen et al showed that inhibition of Akt led to transcriptional induction of PIM1 kinase which in turn regulated the expression of RTKs in prostate cancer [5]. We have shown that a co-targeted approach is more effective compared to single PIM kinase or PI3K-mTOR inhibition, as previously reported in prostate cancer [10].…”
Section: Introductionsupporting
confidence: 81%
“…Cen et al showed that inhibition of Akt led to transcriptional induction of PIM1 kinase which in turn regulated the expression of RTKs in prostate cancer [5]. We have shown that a co-targeted approach is more effective compared to single PIM kinase or PI3K-mTOR inhibition, as previously reported in prostate cancer [10].…”
Section: Introductionsupporting
confidence: 81%
“…BEZ235 inhibits multiple class I PI3K isoforms and mTORC1/2 kinase activity, exerts potent anticancer activity, and attenuates PI3K reactivation and mTORC2-mediated AKT reactivation (Chiarini et al, 2015). It has exhibited antitumor effects in various cancers, including pancreatic cancer, and its synergistic effects have been revealed in combination with numerous drugs, including cytotoxic drugs and target inhibitors https://doi.org/10.4062/biomolther.2021.145 (Murakami et al, 1987;Zhu et al, 2015;Chen et al, 2018;Luszczak et al, 2020;Ruan et al, 2020). However, PI3K inhibitors, including BEZ-235, have been reported to enhance MEK/ERK pathway activation through a negative feedback loop mediated by mTORC2 in pancreatic cancer cells, leading to drug resistance (Soares et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of the PIM inhibitor AZD1208 and the PI3K/mTOR inhibitor BEZ235 (dactolisib) has been investigated in clinical trials. 399 A novel and highly efficient triple PIM/PI3K/mTOR inhibitor AUM302 elicited a superior functional outcome compared to the effects of the combination of AZD1208 and BEZ235; these results may help reduce treatment toxicity in future trials. 399 Overall, the clinical application of PI3K/AKT/mTOR inhibitors is still limited in PCa, and further studies that can identify new biomarkers for patient selection or improve co-targeting strategies are still required to enhance their therapeutic effects.…”
Section: Targeting the Pi3k/akt/mtor Signaling Axismentioning
confidence: 98%